Biphasic lipid extraction from microalgae after PEF-treatment reduces the energy demand of the downstream process - Ioannis Papachristou; Natalja Nazarova; Rüdiger Wüstner; Robin Lina; Wolfgang Frey; Aude Silve (Biotechnology for Biofuels and Bioproducts)
Abstract Background The gradual extrusion of water-soluble intracellular components (such as proteins) from microalgae after pulsed electric field (PEF) treatment is a well-documented phenomenon. This could be utilized in biorefinery applications with lipid extraction taking place after such an ‘incubation’ period, i.e., a post-PEF-treatment step during which the biomass is left undisturbed before any further processing. The goal of this work was to further explore how this incubation could improve lipid extraction. Results Experiments were conducted on wet, freshly harvested Auxenochlorella protothecoides, treated with 0.25 or 1.5 MJ/kgDW and incubated for 24 h. Lipid extraction took place with a monophasic ethanol:hexane:water, 1:0.41:0.04 vol/vol/vol mixture with a 75.6 mL solvent per 1 g of dry biomass ratio. The kinetics of the extraction were studied with samples taken between 10 and 1080 min from fresh and incubated biomass. The yields at 10 min were significantly increased with incubation compared to without (31.2% dry weight compared to 1.81%, respectively). The experimental data were fitted with the Patricelli model where extraction occurs in two steps, a rapid washing of immediate available lipids and a slower diffusion one. During Nile-Red staining of microalgae and microscopy imaging, a shift of emission from both GFP and RFP channels to mostly RFP was observed indicating an increase in the polarity of the environment of Nile-Red. These led to an adaption of a biphasic ethanol:hexane:water 1:6:0.4 vol/vol/vol solvent with 37 mL solvent per 1 g of dry biomass ratio which while ineffective on fresh biomass, achieved a 27% dry weight yield from incubated microalgae. The extraction efficiency in the biphasic route was lower compared to the monophasic (i.e., 69% and 95%, respectively). It was compensated however, by the significant solvent reduction (37 mL to 75.6 mL respectively), in particular the ethanol minimization. For the extraction of 1 L lipids, it was estimated that the energy consumption ratio for the biphasic process was 1.6 compared to 9.9 for monophasic, making clearly the most preferential one. Conclusions This biphasic approach significantly reduces solvent consumption and the respective energy requirement for solvent recovery. Incubation thus could majorly improve the commercialization prospects of the process. Graphical abstract